2008
DOI: 10.1016/j.jinsphys.2008.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Cold hardening processes in the Antarctic springtail, Cryptopygus antarcticus: Clues from a microarray

Abstract: The physiology of the Antarctic microarthropod, Cryptopygus antarcticus, has been well studied, particularly with regard to its ability to withstand low winter temperatures. However, the molecular mechanisms underlying this phenomenon are still poorly understood. 1180 sequences (Expressed Sequence Tags or ESTs) were generated and analyzed, from populations of C. antarcticus. This represents the first publicly available sequence data for this species. A sub-set (672 clones) were used to generate a small microar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 54 publications
2
26
0
Order By: Relevance
“…15 Most studies on the molecular basis of insect cold hardiness conducted to date have been based on the level of the genome, transcriptome and proteome. [15][16][17][18] Despite significant progress in this area, many aspects of the metabolic adaptations underlying diapause and cold hardiness remain undiscovered, especially in non-model organisms. We propose that a metabolomic approach could provide insight into the metabolite composition underlying adaptations in response to unfavourable environmental conditions, such as low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…15 Most studies on the molecular basis of insect cold hardiness conducted to date have been based on the level of the genome, transcriptome and proteome. [15][16][17][18] Despite significant progress in this area, many aspects of the metabolic adaptations underlying diapause and cold hardiness remain undiscovered, especially in non-model organisms. We propose that a metabolomic approach could provide insight into the metabolite composition underlying adaptations in response to unfavourable environmental conditions, such as low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Cuticle differentiation and reorganization is a common response to cold temperatures found in many insects (Dunning et al 2013(Dunning et al , 2014Colinet et al 2012;Purac et al 2008). Although we did not find differential gene expression in this gene family in our brain transcription assays, we did identify two cuticular protein-coding genes (cuticular protein 49AC and 60D ) that were uniquely expressed in overwintering females.…”
Section: Cuticular Proteinsmentioning
confidence: 99%
“…We characterize gene expression profiles of field-collected overwintering C. calcarata and contrast these against previously published active season gene expression profiles in the same species (Rehan et al 2014). Based on existing overwintering gene expression literature (Colinet et al 2007(Colinet et al , 2012Dunning et al 2013Dunning et al , 2014Lee et al 1998;Purac et al 2008;Ragland et al 2010;Rinehart et al 2007Rinehart et al , 2010Robich et al 2007;Torson et al 2015;Qin et al 2005;Yocum et al 2005Yocum et al , 2015, we predict that differential expression would be found in genes relating to heat shock proteins, membrane lipids, cuticular proteins, and cytoskeletal and muscular alterations. We also provide comparisons of our results to previous studies on overwintering gene expression and cold tolerance in other insects, in order to assess whether similar or different genes and pathways are associated with overwintering across taxa.…”
Section: Introductionmentioning
confidence: 96%
“…In the first, animals with 'low' supercooling points (<-15°C) were compared with those with 'high' supercooling points (>-15°C), to determine which genes are responsible for lowering supercooling points (Purać et al, 2008). This microarray contained a subset of 672 expressed sequence tags (ESTs), and thus was not comprehensive.…”
Section: Biochemical and Molecular Mechanisms Of Stress Tolerance In mentioning
confidence: 99%